PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BALAI PELESTARIAN KEBUDAYAAN WILAYAH XX - Presley Nustelu; Olivia Laura Sahertian; Maria Marlyn Tetelepta (Jurnal Administrasi Terapan, 2023)
The XX Region Cultural Preservation Center is the technical implementation unit of the Ministry of Education and Culture in the field of preserving cultural values and is under and responsible for the Director General of Culture. Based on the observations, problems are still found regarding work motivation and performance. This research aims to determine the effect of motivation on employee performance at the XX Region Cultural Conservation Center.The method used in this research was the descriptive method. The population in this study were employees of the XX Region Cultural Preservation Center office, with a population of 31 people and a sample of 30 people. The data were collected through questionnaires. The analysis technique used was simple linear regression.The test results showed that work motivation influences employee performance. Employees who receive good non-financial compensation, who always receive direction at work, have good relationships at work, and receive awards as well as recognition at work have high performance too. Keywords: motivation, employee performance